Can an Incentive-Based approach to rebalancing a Dock-less Bike-share system Work? Evidence from Sacramento, California. (September 2022) - Fukushige, Tatsuya; Fitch, Dillon T.; Handy, Susan
Highlights: Incentivizing users to walk farther is a way of rebalancing a bike-share fleet. The impact of incentives on willingness-to-walk (WTW) to get a bike was examined. Half of bike-share users would use a bike located 8.9-minutes away without an incentive. WTW for incentives at origins and destinations were 3.8 min/US and 4.2 min/US. Results suggest the potential effectiveness of incentives as a rebalancing policy. Abstract: Bike-share services will produce more limited benefits if users cannot find bikes when and where they need them. Bike-share operators must thus have process for "rebalancing" the bikes within the system to ensure that they are available where demanded. A potentially cost-effective strategy for rebalancing bikes is to offer incentives of some sort to users to walk farther to get a bike (origin-based incentive) or bring a bike to the undersupplied area (destination-based incentive). This paper aims to examine bike-share users' willingness-to-walk to pick up a bike or drop off a bike at some distance from their origins or destinations if rewarded and to identify characteristics influencing willingness-to-walk. We use data from a survey of dock-less e-bike-share users conducted in the Sacramento region. The analysis shows that half of the respondents use bike-share if the available bike is located 8.9 min away. Our estimates of willingness-to-walk farther than the mean distance for incentives at origins and destinations were 3.8 min and 4.2 min per dollar, respectively. Our results give operators and policy makers insights into the potential effectiveness of incentives as a strategy for spatially rebalancing bike-share fleets.